It's a Setup 2021
DOI: 10.1093/oso/9780190062217.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Fathering Through the Looking Glass

Abstract: In this chapter, the authors look more closely at fathers’ lives on the streets, the ways in which the criminal justice system intersected with and shaped their lives, their experiences of relating with children and mothers while incarcerated, and their perspectives on fatherhood within the institutional interstices of the streets, police, prisons, and community reentry. Key contradictions are examined that challenge marginalized fathers, including reconciling masculinity on the streets with being available an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Debt from multiple sources results in what Uggen and Stewart (2015) refer to as the "piling on" of debt. For reentering citizens with multiple forms of debt, meeting their probationary requirements and avoiding further sanctions or revocation engenders vulnerability and stress, which can take a variety of adverse forms: drug or alcohol relapse (Horowitz et al 2022), symbiotic harms (Condry and Minson 2020), conflicts and hostilities with intimate partners and co-parents (Black and Keyes 2021;Roman and Link 2017), and reliance on criminal resources (Black and Keyes 2021;Cancian et al 2013;Haney 2018;Holzer et al 2005;Miller and Mincy 2012). While many studies have identified the negative consequences of debt for justice-involved populations, they have typically traced causal sequences stemming from one particular type of debt.…”
Section: Debt Surveillance and Carceral Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Debt from multiple sources results in what Uggen and Stewart (2015) refer to as the "piling on" of debt. For reentering citizens with multiple forms of debt, meeting their probationary requirements and avoiding further sanctions or revocation engenders vulnerability and stress, which can take a variety of adverse forms: drug or alcohol relapse (Horowitz et al 2022), symbiotic harms (Condry and Minson 2020), conflicts and hostilities with intimate partners and co-parents (Black and Keyes 2021;Roman and Link 2017), and reliance on criminal resources (Black and Keyes 2021;Cancian et al 2013;Haney 2018;Holzer et al 2005;Miller and Mincy 2012). While many studies have identified the negative consequences of debt for justice-involved populations, they have typically traced causal sequences stemming from one particular type of debt.…”
Section: Debt Surveillance and Carceral Riskmentioning
confidence: 99%
“…Many studies have critically examined Criminal Legal Financial Obligations (CLFOs)-court fines, restitution orders, and criminal legal fees-and their consequences (Beckett and Harris 2011;Evans 2014;Friedman et al 2021Friedman et al , 2022Harris 2016;Harris et al 2010;Levingston and Turetsky 2007;Mogk et al 2020;Pleggenkuhle 2018;Pogrebin et al 2014). Additionally, the burden and implications of child support arrearages that accumulate during incarceration and extract heavy burdens of debt and constraints on men after release also has been well documented (Black and Keyes 2021;Haney 2018;Turetsky and Waller 2020). Further, the uprising in Ferguson, Missouri after the murder of Michael Brown not only exposed the municipalities' reliance on traffic fines and fees (accounting for 20% of the city's budget) and its disproportionate burden on black drivers (Bastien 2017); it has also drawn attention to the role of driver's license suspensions and related fines and fees that have increased debt among reentering citizens (Council on Economic Advisers 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fantasies and longings emerge from the unanchored moorings of life, leading those most victimized by disinvestment and institutional abandonment to imagine their way out of the chaos and uncertainty into pathways that still designate lives with some modicum of dignity and respect—fatherhood among them. Fatherhood projects new possibilities: for being the fathers that their fathers were not, for leaving the empty promises and risky exigencies of the streets, and for attaining the fading prospects of working-class respectability (Black and Keyes 2020; Edin, Nelson, and Paranal 2004; Nelson et al 2002). These aspirational frames, however, are battered by the realities of unemployment, precarious employment, and dwindling state support.…”
Section: The Casualization Of Family Relationships and The New Fatherhoodmentioning
confidence: 99%
“…In this regard, “deadbeat dads” join the ranks of “welfare queens” in advancing categories of disrepute and in deserving state surveillance and management. The symbolism of the deadbeat dad in categorizing marginalized fathers was articulated and enacted by magistrates in child support enforcement courts, staff in responsible fatherhood programs, social workers in welfare offices, police officers in deadbeat dad roundups, and probation and parole officers in routine office meetings (Black and Keyes 2020).…”
Section: Working the Boundariesmentioning
confidence: 99%